(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Monetary policy, a critical tool in the arsenal of central banks, plays a pivotal role in shaping the economic trajectory of nations. This paper explores the intricate relationship between monetary policy and economic growth, emphasizing the channels through which monetary interventions influence macroeconomic outcomes. We examine theoretical frameworks, empirical evidence, and case studies to elucidate how interest rate adjustments, money supply changes, and quantitative easing affect economic performance. The findings underscore the importance of a balanced and well-calibrated monetary approach to sustain growth while mitigating inflationary and recessionary pressures.